Dendritic cells in the tumor microenvironment: prognostic and theranostic impact. (April 2020) - Verneau, Johanna; Sautés-Fridman, Catherine; Sun, Cheng-Ming
Highlights: All subsets of DCs can be found in tumor. The density and maturation state of several DC subsets correlate with positive prognosis Conventional type 1 DCs (cDC1) are critical antigen-presenting cells that are required for the activation of anti-tumor cytotoxic T lymphocytes and T cell migration to tumor Conventional type 2 DCs (cDC2) are important to activate CD4 T cells which are necessary for a durable CTL response to be established The presence of pDCs is generally correlate with poor prognosis. However, activated pDCs may still have potential to induce strong anti-tumor responses. Abstract: Among all immune cells, dendritic cells (DC) are the most potent APCs in the immune system and are central players of the adaptive immune response. There are phenotypically and functionally distinct DC populations derived from blood and lymphoid organ including plasmacytoid DC (pDC), conventional DC (cDC1 and cDC2) and monocyte-derived DC (moDC). The interaction between these different DCs and tumors is a dynamic process where DC-mediated cross-priming of tumor specific T cells is critical in initiating and sustaining anti-tumor immunity. Their presence within the tumor tends to induce T cell responses and to reduce cancer progression and is associated with improved patient survival. This review will focus on the distinct tumor-associated DCs (TADC) subsets in the tumor microenvironment (TME), their roles in tumor immunology and their prognostic and/or predictive impact in human cancers. The development of therapeutic immunity strategies targeting TADC is promising to enhance their immune-stimulatory capacity in cancers and improve the efficacy of current immunotherapies including immune checkpoint inhibitor (ICI) blockade and DC-based therapies.